2010
DOI: 10.2119/molmed.2010.00178
|View full text |Cite
|
Sign up to set email alerts
|

A Paradoxical Role for Myeloid-Derived Suppressor Cells in Sepsis and Trauma

Abstract: Myeloid-derived suppressor cells (MDSCs) are a heterogenous population of immature myeloid cells whose numbers dramatically increase in chronic and acute inflammatory diseases, including cancer, autoimmune disease, trauma, burns and sepsis. Studied originally in cancer, these cells are potently immunosuppressive, particularly in their ability to suppress antigen-specific CD8 + and CD4+ T-cell activation through multiple mechanisms, including depletion of extracellular arginine, nitrosylation of regulatory prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
322
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(328 citation statements)
references
References 63 publications
6
322
0
Order By: Relevance
“…Our current results demonstrate that tumor infiltration by MDSCs is tumor-dependent and can be associated with a high frequency and absolute number of MDSCs infiltrating into the spleen, liver, lungs, tumor tissue, and PB. It was previously shown that murine MDSCs express low or intermediate levels of CD11c [52] while other studies have suggested higher levels of CD11c expression on MDSCs [25,49,[53][54][55]. In the present study we excluded lymphocytes from analysis (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Our current results demonstrate that tumor infiltration by MDSCs is tumor-dependent and can be associated with a high frequency and absolute number of MDSCs infiltrating into the spleen, liver, lungs, tumor tissue, and PB. It was previously shown that murine MDSCs express low or intermediate levels of CD11c [52] while other studies have suggested higher levels of CD11c expression on MDSCs [25,49,[53][54][55]. In the present study we excluded lymphocytes from analysis (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Patients with PICS have a persistent acute phase response (characterized by elevated CRP and undetectable pre-albumin levels) with elevated white blood cell counts but with a very low percentage of lymphocytes[35]. Recent laboratory studies demonstrate the long-term emergence of myeloid derived suppressor cells (MDSCs) during sepsis: immature innate immune cells that suppress lymphocytes but simultaneously cause persistent inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent laboratory studies demonstrate the long-term emergence of myeloid derived suppressor cells (MDSCs) during sepsis: immature innate immune cells that suppress lymphocytes but simultaneously cause persistent inflammation. We believe they play central role in PICS and this is a current focus of our ongoing research related to MOF pathogenesis[35]. Similarly, emerging evidence suggests that altered homeostasis during AKI leads to an activated innate and adaptive immune response and distant organ dysfunction [22, 36-40].…”
Section: Discussionmentioning
confidence: 99%
“…The physiological role of MDSC is thought to lie in the regulation of immune responses to infection and after traumatic stress [3][4][5]. However, increased frequencies of immature myeloid cells with suppressive functions have also been observed in many diVerent types of cancer [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%